The Invention of Convention - Larcom, Joan (The Australian journal of anthropology, 1982)
The traditional past of the people of South-West Bay, Malekula, featured a great deal of cultural borrowing. Like most Christians in Vanuatu, their negative attitude to a 'pagan' past has been changed into one of positive interest by the recent national emphasis on kastorn. Their older perception of kastorn as commodity - knowledge, rituals, objects, etc. to be bought, sold or exchanged at will - has been supplemented by the more wide- spread notion of kastom as a stable body of traditions, unshared as well as shared. The validatory potential of kastorn is being realized as people re-evaluate and reinvent their past, exploiting lacunae in customary knowledge by imaginative citation of the written ethnographic word. Contemporary needs are apparently more effectively satisfied by reference to fixed truths rather than to fluid and dynamic representations of culture.